2021
DOI: 10.1186/s12913-021-06308-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of frontline Pakistani emigrant physicians combating COVID-19 in the United Kingdom: a qualitative phenomenological analysis

Abstract: Background This study aims to explore the experiences, beliefs, feelings, and challenges faced by Pakistani migrant doctors working in the United Kingdom in times of the COVID-19 pandemic. The qualitative study aims to explore the lived experiences, beliefs, feelings, and challenges faced by Pakistani migrant physicians working in the United Kingdom during the COVID-19 pandemic. Methods An exploratory phenomenological approach was used to collate d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Qualitative studies conducted with HWs in the UK during the early months of the pandemic identified concerns at the time; these included: inadequate access to personal protective equipment (PPE) and COVID-19 testing; rapidly changing and inconsistent guidelines; a lack of training; communication challenges; increased workload and rapidly changing work conditions [ 7 12 ]. Studies also highlighted the impact of pandemic-related stressors and work conditions on the mental health and wellbeing of HWs, both in the UK [ 12 14 ] and internationally [ 15 20 ]. Following the first wave of COVID-19, calls were made to learn lessons for future waves and pandemics [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies conducted with HWs in the UK during the early months of the pandemic identified concerns at the time; these included: inadequate access to personal protective equipment (PPE) and COVID-19 testing; rapidly changing and inconsistent guidelines; a lack of training; communication challenges; increased workload and rapidly changing work conditions [ 7 12 ]. Studies also highlighted the impact of pandemic-related stressors and work conditions on the mental health and wellbeing of HWs, both in the UK [ 12 14 ] and internationally [ 15 20 ]. Following the first wave of COVID-19, calls were made to learn lessons for future waves and pandemics [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of 'proven' pharmaceutical interventions, some studies reported an increase in supportive care, which often involved higher patient contact and emotional work, and disproportionally impacted nurses (including via increased risk of infection). 50 70 72 73 A notable motif throughout the literature was the affecting presence of pandemic death, which came to be known through the materiality of objects of care such as body bags and beds. Many healthcare workers had no experience handling dead bodies prior to the pandemic and this lack of knowledge, along with changes to processes for managing death in the hospital, meant that bodies were often not prepared in accordance with the religious or cultural beliefs of patients.…”
Section: Open Accessmentioning
confidence: 99%
“…Some studies even suggest that doctors aim of attaining highly specialized skills, that can later be used to the benefit of their home country. 1,11 But it is important to remember that the grass isn't always greener on the other side. There Is a significant mismatched between what IMGs expect and what the UK training system has to offer.…”
Section: Introductionmentioning
confidence: 99%